Ionization dynamics of XUV excited clusters: the role of inelastic electron collisions. (17th July 2015) - Müller, M; Schroedter, L; Oelze, T; Nösel, L; Przystawik, A; Kickermann, A; Adolph, M; Gorkhover, T; Flückiger, L; Krikunova, M; Sauppe, M; Ovcharenko, Y; et al.
Abstract: We report on the ionization and nanoplasma dynamics of small xenon clusters irradiated by intense, short pulses of a short-wavelength free-electron laser. Fluorescence spectroscopy indicates that inelastic electron collisions play a prominent role in the formation of the highest charge states. From the spectral distribution an electron temperature of 27 eV is deduced which corresponds to the average excess energy of the Auger- and photoelectrons ionized from individual atoms but trapped in the cluster core. This suggests that fluorescence spectra reflect a very early stage within the nanoplasma dynamics and shows how a part of the kinetic energy of the plasma electrons trapped in the cluster potential is transferred to the ions.